"Revenue Generating Machines"? London's Local Housing Companies and the Emergence of Local State Rentierism. Issue 2 (3rd September 2021) - Penny, Joe
Abstract: Since 2010, faced with deep austerity measures, 27 London councils have set up a housing company to acquire, develop, and manage housing. Following 40 years of privatisation, these council‐owned companies have been celebrated as a post‐neoliberal municipal alternative to the hegemony of market‐led urban policy. By developing commodified real estate and monetising rising land values, they promise to deliver well‐designed housing, generate long‐term fiscal rents, and secure local state autonomy. Drawing on in‐depth empirical research, this paper develops a situated political economic critique of the limitations, contradictions, and risks of local housing companies in London. Framed as a "critical case", providing insight into the politics of speculative urban provisioning and land value extraction, I argue that local housing companies represent a mode of municipal statecraft—a local state rentierism—that leans into and reproduces a political economy of financialisation and rentierism with potentially long‐term implications for collective urban provisioning.